2009
DOI: 10.1210/jc.2008-2327
|View full text |Cite
|
Sign up to set email alerts
|

High Aromatase Expression in Uterine Leiomyoma Tissues of African-American Women

Abstract: Leiomyoma tissues from African-American women contained the highest level of aromatase expression, which may result in elevated tissue concentrations of estrogen, and account for the higher prevalence and earlier incidence. Analysis of leiomyoma tissue for biomarkers may predict the response to hormonal treatments such as aromatase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 16 publications
2
83
1
3
Order By: Relevance
“…Aromatase activity was shown to be present in human uterine leiomyomas and it has been suggested that it may contribute to the development of these tumors [13]. Sumitani et al [8] and Ishikawa et al [21 ]found higher levels of aromatase in leiomyoma when compared with adjacent myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Aromatase activity was shown to be present in human uterine leiomyomas and it has been suggested that it may contribute to the development of these tumors [13]. Sumitani et al [8] and Ishikawa et al [21 ]found higher levels of aromatase in leiomyoma when compared with adjacent myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests the presence of interindividual variation in the use of alternative promoters 18,19 and even usage differences between ethnic groups. 20 The author recently proposed the hypothesis that person-to-person variation in the use of alternative regulatory elements may extend to both gene promoters and enhancers. 21 This hypothesis predicts that, in presence of inter-individual variation in the use of redundant regulatory elements (eg, gene promoters and enhancers) and if functional SNPs are located inside those elements, the observed effects of these functional variants would be attenuated by a factor equal to the proportion of chromosomes in the population using their respective regulatory element.…”
Section: Alternative Use Of Redundant Enhancersmentioning
confidence: 99%
“…The underlying mechanism is the inhibition of the aromatase enzyme, which is the enzyme that catalyzes the conversion of androgenic substances into estrogens [41]. Recent reports have suggested that aromatase is expressed to a greater extent in uterine leiomyoma tissues of African-American women compared to Caucasian women, which may contribute to the higher incidence of ULMs in African American women [42]. Aromatase inhibitors have been shown to be effective against fibroids in limited short term studies with dosing regimens that included 2.5 mg per day of letrozole and 1 mg per day of anastrozole [43].…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%